Cognitive reactions of nurses exposed to cancer patients' traumatic experiences: A qualitative study to identify triggers of the onset of compassion fatigue. Issue 2 (6th October 2017) - Fukumori, Takaki; Miyazaki, Atsuko; Takaba, Chihiro; Taniguchi, Saki; Asai, Mariko
Abstract: Objective: Nurses in cancer care are considered to be at risk for compassion fatigue because they are frequently exposed to patients' traumatic experiences. However, only a few effective empirical studies have been conducted in this field, and cognitive factors in particular have not been sufficiently studied. This study aims to describe the components of nurses' cognitive reactions from their exposure to cancer patients' traumatic experience to the onset of compassion fatigue. Methods: In this qualitative study, 30 nurses in cancer care were purposively selected. Data were collected through semistructured interviews and analyzed by using content analysis and the constant comparative method. Results: Forty attributes were identified from 613 statements and classified into 11 categories: sense of professional inadequacy, compassion for patients and their families, desire to support patients and their families, rumination on oneself or one's family, sense of professional mission, dissatisfaction with medical staff, desire to integrate with colleagues, desire to avoid one's duties, conflict between one's belief and reality, reconsideration of the meaning of life, and sense of powerlessness over cancer. Conclusions: This study identified important components of cognitive reactions of nurses who encounter the traumatic experiences of cancer patients in Japan. This information can contribute to the understanding of the onset of compassion fatigue and provide the foundation for nurses in cancer care to avoid and recover from compassion fatigue.